Transient Phenomena during the Three-Phase 300MVA Transformer Energization on the Transmission Network - Emir Alibašić; Predrag Marić; Srete N Nikolovski (Institute of Advanced Engineering and Science, 2016)
Connecting the transformer to the network may incur inrush current, which is significantly higher than the rated current of the transformer. The main cause of this phenomenon lies in the nonlinearity of the magnetic circuit. The value of the inrush current depends of the time moment of the energization and the residual magnetism in the transformer core. While connecting, the operating point of the magnetization characteristic can be found deep in the saturation region resulting in occurrence of large transformer currents that can trigger the transformer protection. Tripping of protection immediately after the transformer energization raises doubts about the transformer health. Inrush current can cause a number of other disadvantages such as the negative impact on other transformers connected on the same busbar; the increase of the transformer noise due to the large current value, the increase of the voltage drops in the network. The paper presents a simulation of the 300 MVA transformer energization using the MATLAB/Simulink software.